Concussion Clinical Profiles Screening (CP Screen) Tool: Preliminary Evidence to Inform a Multidisciplinary Approach. Issue 2 (17th January 2020) - Kontos, Anthony P; Elbin, R J; Trbovich, Alicia; Womble, Melissa; Said, Azkya; Sumrok, Vanessa Fazio; French, Jonathan; Kegel, Nathan; Puskar, Alicia; Sherry, Natalie; Holland, Cyndi; Collins, Michael
Abstract: BACKGROUND: Current concussion symptom inventories emphasize total number or symptoms and severity and overlap with other conditions, such as mental health disorders, which may limit their specificity and clinical utility. OBJECTIVE: To develop and test the reliability and validity of a new Concussion Clinical Profiles Screening tool (CP Screen) in both healthy controls and concussed. METHODS: CP Screen is a 29-item self-report, clinical profile-based symptom inventory that measures the following 5 concussion clinical profiles: 1) anxiety/mood, 2) cognitive/fatigue, 3) migraine, 4) ocular, and 5) vestibular; and the following 2 modifying factors: 1) sleep and 2) neck. Post-Concussion Symptom Scale (PCSS), vestibular/ocular motor screening (VOMS) tool, and Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) were conducted. CP Screen was administered in community a concussion surveillance program and 2 sports medicine concussion clinics. Responses include 248 athletes, 121 concussed, and 127 controls, enrolled between 2018 and 2019. RESULTS: Internal consistency of the CP Screen in the control (Cronbach's alpha = .87) and concussed (Cronbach's alpha = .93) samples was high. Moderate to high correlations among the CP Screen factors and PCSS factors and VOMS items, supporting concurrent validity. ROC curve analysis for identifying concussed from controls was significant ( P  < .001) for all CP Screen factor and modifier scores with excellent AUCs for migraine (.93), ocular (.88), vestibular (.85), and cognitive (.81) factors, demonstrating predictive validity. CONCLUSION: The CP Screen demonstrated strong reliability, concurrent validity with commonly used concussion assessment (ie, PCSS, VOMS, and ImPACT), and predictive validity for identifying concussion. The CP Screen extends current symptom inventories by evaluating more specific symptoms that may reflect clinical profiles and inform better clinical care.